(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the interpretation of biology in chemistry, physics and mathematical expressions, cognitive research, the level of cognitive learning, cognitive development in the implementation of integrated teaching in biology classes on the basis of STEAM education.